Stability-Indicating HPLC Method for isoflavones aglycones analysis from Trifolium pratense L. extract - Martiny, Simony; Waszczuk, Mairique; Kaiser, Samuel; Nemitz, Marina Cardoso; Bassani, Valquiria Linck (Drug Analytical Research, 2026)
The purpose of this study was to develop and validate a fast HPLC stability-indicating method for simultaneously quantifying the four main isoflavones in Trifolium pratense. Validation procedures followed the ICH requirements for complex matrices. The stability-indicating tests were performed by exposing the isoflavones to conditions of forced degradation and further analysis for verifying the formation of degradation products and their possible interferences in the HPLC analysis. The major isoflavones of Trifolium pratense proved to be stable against acid and oxidative media, thermodegradation, and photodegradation. However, they proved to be unstable in alkaline media, even for short periods of exposure like 2h. In this condition, in addition to the peaks corresponding to isoflavones, the HPLC analysis showed the presence of three additional peaks which were eluted at different retention times to the reference substances, without interfering in the quantification of the four analytes of interest, formononetin, biochanin A, daidzein and genistein. The method was validated following ICH guidelines showing to be specific, linear, precise, accurate, and robust. This first report concerning a stability-indicating method revealed that the proposed HPLC method reliably quantify the isoflavones and separate them from the degradation products in a short time of analysis.